SLANG WORDS FOUND ON “TO ALL THE BOYS ALWAYS AND FOREVER” MOVIE - I Wayan Adi Nugraha Nugraha; I Komang Sulatra (Yavana Bhasha : Journal of English Language Education, 2023)
Slang is a variety of language used mainly by teenagers to communicate with group members in informal situations. This research aims at identifying slang words and categorizing the type of slang used in the film "To All the Boys Always and Forever". This is a descriptive qualitative research. The data are limited to the main character in the film, namely Lara Jean and Peter Kavinsky. The data collection method used in this research was observation method, namely by downloading film, watching movies and choosing words that belong to slang in the dialogue. This study applied the theory of types of slang by Kipfer and Chapman (2007). The data analysis were done by using descriptive qualitative method with the stages of data collection, data reduction, presentation of data and drawing conclusions. This research found 11 data of slang words, which are divided into 2 types, such as; namely primary slang and secondary slang. There are ten data of primary slang and only one data of secondary slang.